2021
DOI: 10.1186/s12879-021-06596-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID-19 progression on day 5 from symptoms onset

Abstract: Background A major limitation of current predictive prognostic models in patients with COVID-19 is the heterogeneity of population in terms of disease stage and duration. This study aims at identifying a panel of clinical and laboratory parameters that at day-5 of symptoms onset could predict disease progression in hospitalized patients with COVID-19. Methods Prospective cohort study on hospitalized adult patients with COVID-19. Patient-level epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Since the first outbreak of COVID-19, this pandemic has negatively affected the capacity of local and regional healthcare systems worldwide, resulting in the temporal exhaustion of in-hospital medical services ( 2 , 3 ). The necessity of hospitalization due to COVID-19 is largely affected by the presence of respiratory failure, which typically develops several days (at least 3 days) after the onset of the first symptoms ( 4 , 5 ). Therefore, investigating the initial immune response in the early phase of SARS-CoV-2 infection is important because it may be related to the development of respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first outbreak of COVID-19, this pandemic has negatively affected the capacity of local and regional healthcare systems worldwide, resulting in the temporal exhaustion of in-hospital medical services ( 2 , 3 ). The necessity of hospitalization due to COVID-19 is largely affected by the presence of respiratory failure, which typically develops several days (at least 3 days) after the onset of the first symptoms ( 4 , 5 ). Therefore, investigating the initial immune response in the early phase of SARS-CoV-2 infection is important because it may be related to the development of respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical parameters, such as age, coexisting diseases, lymphocyte count, D-dimer and lactate dehydrogenase (LDH), have been reported as predictors of COVID-19 progression since the COVID-19 pandemic began. Although prediction models using some of these parameters for the progression of COVID-19 have been well developed, there have been few reports about the rebound of COVID-19 13 14. One retrospective study reported that patients with rebound pneumonia tended to terminate steroids earlier in the disease process and showed a poor prognosis 15.…”
Section: Introductionmentioning
confidence: 99%
“…Bhaskar, et al reported that anti-inflammatory agents have a mechanism to block hyperinflammatory conditions by targeting cytokine-related signal transduction pathways and have pharmacological properties in which the risk of immunosuppression of anti-inflammatory agents may be greater than the risk of COVID-19 for immunocompromised patients ( Bhaskar et al, 2020 ). In the literature related to the clinical course of COVID-19, Gentilotti et al reported that it usually takes 5–7 days from the onset of symptoms of COVID-19 to hospitalization, which is an inflection point where respiratory symptoms are likely to worsen due to the action of excessive inflammation ( Gentilotti et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the target population of this study design, we judged that inpatients would be the most appropriate given that it usually takes between 5 and 7 days from symptom onset to hospitalization for COVID-19 which is an inflection point for respiratory symptoms to likely worsen as a function of excessive inflammation ( Gentilotti et al, 2021 ). Considering the timing of the anti-inflammatory treatment and the results of anti-inflammatory agent trials for COVID-19, it seemed appropriate to proceed with clinical trials of anti-inflammatory drugs for COVID-19 for hospitalized patients with severe or a higher severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%